Anterior versus posterior approach for the treatment of cervical compressive myelopathy due to ossification of the posterior longitudinal ligament: A systematic review and meta-analysis. (March 2016) - Feng, Fan; Ruan, Wenfeng; Liu, Zhengye; Li, Yi; Cai, Lin
Abstract: Purpose: The purpose of the study is to perform a systematic review and meta-analysis to evaluate the clinical results of anterior and posterior approaches for the treatment of cervical compressive myelopathy due to cervical ossification of the posterior longitudinal ligament (OPLL). Methods: Randomized controlled trials or non-randomized controlled trials published since January 1995 to October 2015 that compared the clinical effectiveness of anterior and posterior surgical approaches for the treatment of cervical OPLL were acquired by a comprehensive search in three electronic databases (PubMed, EMBASE, Cochrane library). A total of 13 studies (1050 patients) were included in this systematic review and meta-analysis. Result: The results indicated that no statistically significant differences between the anterior group and posterior group in terms of preoperative JOA score [P = 0.16, SMD = 0.1 (−0.04, 0.23)] and recovery rate of patients with canal-occupying ratio < 50%–60% [p = 0.89, SMD = 0.03 (−0.35, 0.41)]. The anterior group showed higher postoperative JOA score [P < 0.05, SMD = 0.23 (0.05, 0.41)], overall recovery rate (regardless of canal-occupying ratio) [P < 0.01, SMD = 0.79 (0.31, 1.27)], especially a significant higher recovery rate of patients with canal-occupying ratio > 50%–60% [P < 0.01, SMD = 1.50 (0.52, 2.47)]. However, it also revealed that the postoperative complication rate [P < 0.05, OR = 1.90 (1.08, 3.36)], blood loss [P < 0.01, SMD = 0.63 (0.34, 0.93)] and operative time [P < 0.01, SMD = 1.86 (1.07, 2.65)] were significantly higher. Conclusion: Based on the results above, anterior approach surgery was associated with better overall (regardless of the canal-occupying ratio) postoperative neural function than posterior approach in the treatment of cervical compressive myelopathy due to OPLL. We thought anterior approach especially preferable to patients with canal-occupying ratio > 50%–60%, although it leads to a higher surgical trauma and incidence of surgery-related complications. Posterior approach surgery was relatively safer with lower surgical trauma and incidence of complications. We also suggest posterior approach for patients with canal-occupying ratio < 50%–60%, since the postoperative neural function was similar between the two groups for this part of patients. Highlights: The optimal surgical strategy for cervical OPLL remains controversial. We have compared two surgery approaches in treatment of cervical OPLL. Based on the results, we thought anterior approach especially preferable to patients with canal-occupying ratio > 50%–60% and posterior approach suggested for patients with canal-occupying ratio < 50%–60%.